2019
DOI: 10.1182/blood-2019-126416
|View full text |Cite
|
Sign up to set email alerts
|

Transformation Mechanisms of the Nfia-ETO2 Fusion Gene Associated with Pediatric Pure Acute Erythroleukemia

Abstract: Pure erythroleukemia (PEL) is a very aggressive, but poorly understood form of acute myeloid leukemia characterized by malignant accumulation of erythroid progenitor cells. A novel t(1;16)(p31;q24) chromosomal translocation leading to expression of a fusion between the nuclear factor I A (NFIA) and the ETO2 transcriptional co-regulator (a.k.a. CBFA2T3 or MTG16) has been identified in pediatric patients with PEL. Based on the function of the fusion partners, we hypothesized that NFIA-ETO2 (N-E) might initiate P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Forkhead box proteins are a group of transcriptional factors implicated in different cellular functions such as differentiation, proliferation and senescence ( 72 ) to affect hematopoietic tumor, while EP300 suppresses leukemia development in myelodysplastic syndromes through inhibiting Myb ( 73 ). It has also been reported that mutations in the human Ank1 ( 74 , 75 ), Runx2 ( 76 79 ), Nfia ( 80 ), Hmga2 ( 81 ), and Klf1 ( 82 , 83 ) genes caused diseases of the hematopoietic system, such as hereditary spherocytosis, fetal anemia, myelodysplastic syndrome, and acute erythroleukemia. The diseases caused by mutations in these genes strongly support our speculation that the transcription factors Ank1, Runx2, Nfia, Hmga2, Klf1, and Bmyc may play important roles in monocyte development.…”
Section: Discussionmentioning
confidence: 99%
“…Forkhead box proteins are a group of transcriptional factors implicated in different cellular functions such as differentiation, proliferation and senescence ( 72 ) to affect hematopoietic tumor, while EP300 suppresses leukemia development in myelodysplastic syndromes through inhibiting Myb ( 73 ). It has also been reported that mutations in the human Ank1 ( 74 , 75 ), Runx2 ( 76 79 ), Nfia ( 80 ), Hmga2 ( 81 ), and Klf1 ( 82 , 83 ) genes caused diseases of the hematopoietic system, such as hereditary spherocytosis, fetal anemia, myelodysplastic syndrome, and acute erythroleukemia. The diseases caused by mutations in these genes strongly support our speculation that the transcription factors Ank1, Runx2, Nfia, Hmga2, Klf1, and Bmyc may play important roles in monocyte development.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, NFIA-ETO2 -expressing erythroblasts harboring one of the most frequent cancer and AEL-associated TP53 mutation, TP53 R248Q , could be serially plated in MC and when transplanted into irradiated recipients, induced a fully penetrant transplantable lethal erythroleukemia-like disease characterized by hepatosplenomegaly, anemia, thrombocytopenia, and the presence of erythroid progenitor cells on peripheral blood smear. 102 Molecular studies suggested that NFIA-ETO2 primarily blocks erythroid differentiation by repressing NFIA as well as GATA1 target genes, and that the TP53 R248Q mutation endowed cells with aberrant stemness and aberrant activity of the polycomb complex 2 (PRC2). In addition, similar to other ETO-protein containing fusions, NFIA-ETO2 immortalized cells may also be sensitive to small peptides that disrupt ETO-NHR-domain-mediated protein/protein interactions, suggesting a potential therapeutic vulnerability.…”
Section: From Tumor Viruses To Rationale Erythroleukemia Modelsmentioning
confidence: 99%
“…In addition, similar to other ETO-protein containing fusions, NFIA-ETO2 immortalized cells may also be sensitive to small peptides that disrupt ETO-NHR-domain-mediated protein/protein interactions, suggesting a potential therapeutic vulnerability. 102 , 112 …”
Section: From Tumor Viruses To Rationale Erythroleukemia Modelsmentioning
confidence: 99%
See 2 more Smart Citations